Immune Cytolytic Activity as an Indicator of Immune Checkpoint Inhibitors Treatment for Prostate Cancer - Gao, Ze; Tao, Yiran; Lai, Yiming; Wang, Qiong; Li, Zean; Peng, Shirong; Chen, Junxiu; Cai, Wenli; Li, Kaiwen; Huang, Hai (Frontiers in Bioengineering and Biotechnology, 2020)
Immune checkpoint inhibitors (ICIs) treatment is becoming a new hope for cancer treatment. However，most prostate cancer patients do not benefit from it. In order to achieve the accuracy of ICIs treatment in prostate cancer and reduce unnecessary costs for patients, we have analyzed the data from TCGA database to find indicators that can assist the choice of treatment. By analyzing the tumor mutation burden and immune infiltration in prostate cancer, we found the expression of immune cells in different immune infiltration groups. The commonly used markers of ICIs, expressed on CD8+ T cells, are highly expressed in the high immune group. Then we used the immune cytolytic activity (CYT) to determine its relationship with the target of ICIs treatment. Through the analysis of CYT score and the ligands of immune checkpoints, we found that there was a significant correlation between them. With the increase of CYT score, the expression of CD80/86, PD-L1/L2, TNFSF14 and LGALS9 also increased gradually. Similarly, CD8+ T cells were significantly increased in the CYT high group compared with the CYT low group in PRAD. The present research provides novel insights into the immune microenvironment of PRAD and potential immunotherapies. The proposed CYT score is a clinically promising indicator that can serve as a marker to assist anti-PD-L1 or other ICIs treatment. At the same time, it also provides a basis for the selection of other immune checkpoint drugs in PRAD patients.